A framework of penta-helix model to improve the sustainable competitiveness of the wine industry in Baja California based on innovative natural resource management - Cabrera-Flores, Mayer Rainiero (My University, 2020)
This paper presents an innovative natural resource management framework for the wine industry based on the Penta-Helix Model and Open Innovation features. As an initial activity, a particular survey was designed in order to be applied to a lot of companies to determine the necessities perception related to the elements of sustainable competitiveness. In fact, the evaluation of sustainable competitiveness is the key to the innovate framework proposed. Considering the results related to the elements of sustainable competitiveness (i.e. natural capital, social capital, intellectual capital and governance efficiency), a flow chart for innovative natural resource management as a first stage is proposed as part of a complete framework called Penta-Helix stakeholder management. In particular, water availability and quality is the most important challenge detected related to natural resource management.
Keywords: Penta-Helix; Wine industry; Campus Ensenada